Urgensi Pengaturan Pengawasan Decentralized Finance Sebagai Perlindungan Hukum Bagi Pengguna Aset Kripto Dalam Terjadi Fraud (RechtJiva, 2024)
In this study, the author addresses the issue of the absence of regulations concerning the Decentralized Finance (DeFi) system as a development within the cryptocurrency asset ecosystem. The Decentralized Finance system is capable of establishing a decentralized financial ecosystem using cryptocurrency assets. The regulatory framework in Indonesia has yet to provide adequate legal protection for cryptocurrency asset customers engaging in transactions within the Decentralized Finance system. This research employs a normative juridical method, utilizing a statute approach, a conceptual approach, and a comparative approach. The primary, secondary, and tertiary legal materials obtained by the author are analyzed using grammatical and systematic interpretation methods. The author concludes that the urgency of regulating the supervision of the Decentralized Finance system lies in its potential to provide legal protection for cryptocurrency asset customers by minimizing the risk of losses, particularly given society's difficulty in adapting to the rapid advancements in financial technology. The regulatory conceptualization proposed by the author, based on comparisons with regulations related to cryptocurrency and Decentralized Finance in Singapore, Australia, the European Union, and the FATF, suggests tightening the assessment and compliance processes for service providers and/or parties conducting business activities with service providers. This includes requiring specific certifications or licenses for the operation of Decentralized Finance systems, identifying the status and role of each party or entity involved, establishing governance protocols and emergency schemes, mandating reporting obligations and transparency for services and the cryptocurrency assets used within the system, and ensuring compliance oversight concerning the scale and scope of service products.